2017
DOI: 10.1090/conm/695/14003
|View full text |Cite
|
Sign up to set email alerts
|

Quasiconformal Teichmüller theory as an analytical foundation for two-dimensional conformal field theory

Abstract: The functorial mathematical definition of conformal field theory was first formulated approximately 30 years ago. The underlying geometric category is based on the moduli space of Riemann surfaces with parametrized boundary components and the sewing operation. We survey the recent and careful study of these objects, which has led to significant connections with quasiconformal Teichmüller theory and geometric function theory.In particular we propose that the natural analytic setting for conformal field theory i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…The future solution of this problem will depend on the further study of the moduli space of Riemann surfaces with parametrized boundaries, including in particular the study of a conjecture by the author on meromorphic functions on this moduli space. See [RS1]- [RS3] and [RSS1]- [RSS5] for results on this moduli space.…”
Section: A Program To Construct Conformal Field Theoriesmentioning
confidence: 99%
“…The future solution of this problem will depend on the further study of the moduli space of Riemann surfaces with parametrized boundaries, including in particular the study of a conjecture by the author on meromorphic functions on this moduli space. See [RS1]- [RS3] and [RSS1]- [RSS5] for results on this moduli space.…”
Section: A Program To Construct Conformal Field Theoriesmentioning
confidence: 99%
“…These are required for the construction of two-dimensional conformal field theory from vertex operator algebras. A comprehensive review can be found in [52]. The sewing technique is also of independent interest in Teichmüller theory.…”
Section: 4mentioning
confidence: 99%
“…This can be thought of as a characterization of the possible Fourier series on S 1 obtained by pulling back elements of D(Σ). This characterization relates to the so-called Segal-Wilson Grassmannian, and has applications to two-dimensional conformal field theory and to Teichmüller theory, see D. Radnell, E. Schippers and W. Staubach [14,15].…”
Section: Introductionmentioning
confidence: 99%